1979
DOI: 10.1159/000260380
|View full text |Cite
|
Sign up to set email alerts
|

A 3-Year Clinical Trial of Calcium Carbonate Dentifrice Containing Calcium Glycerophosphate and Sodium Monofluorophosphate

Abstract: A double-blind clinical study extending over 3 years is reported. Two examiners independently examined 944 subjects to evaluate the efficacy of a calcium carbonate-based sodium monofluorophosphate dentifrice and a similar sodium monofluorophosphate dentifrice but with calcium glycerophosphate as an additive. Subjects brushed only at home withouth supervision. Subjects in booth treatment groups showed a statistically significant lower caries incidence than subjects in the control group. Both independent examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…In the remaining effort, the findings show no important difference be tween formulations. Finally, two studies have reported on the effect of adding calcium glycerophosphate (CaGP) to the MFP for mulations [Naylor and Glass, 1979;Mainwaring and Naylor. 1983].…”
Section: Williamsonmentioning
confidence: 99%
See 1 more Smart Citation
“…In the remaining effort, the findings show no important difference be tween formulations. Finally, two studies have reported on the effect of adding calcium glycerophosphate (CaGP) to the MFP for mulations [Naylor and Glass, 1979;Mainwaring and Naylor. 1983].…”
Section: Williamsonmentioning
confidence: 99%
“…It is based upon evidence indicating that fluoridated hydroxyapatite formation is increased by the addition of CaGP [Forwardet al, 1975; and caries inhibition in rats is enhanced [1974] 32 James et al [1977] 30 [Bolderson, et al, 1975;, Nonetheless, these studies are of interest within the context of this discussion since they do employ calcium-augmented formu lations. In the first study by Naylor and Glass [1979] the addition of CaGP failed to provide significantly greater benefit relative to a conventional MFP dentifrice. In the sec ond study [Mainwaring and Naylor, 1983] subjects receiving the active control (MFP) developed 9.30 new lesions over 4 years while those using the MFP/CaGP formula tion developed 8.17, a saving of 1.13 surfaces or a reduction of just 13%.…”
Section: Williamsonmentioning
confidence: 99%
“…As the plaque becomes acidic, calcium and phosphate are released at the expense of hydrogen ions and protect the enamel against demineralization by common ion effects [Dawes and Jenkins, 1962;Kleinberg et al, 1983]. Fluoride has been suggested as an agent to stimulate plaque mineralization [Pearce, 1981], There is clinical evidence for an additive cariesinhibitory effect of calcium glycerophosphate and fluoride [Naylor and Glass, 1979;Mainwaring and Naylor, 1983]. This effect is likely to be explained by increased mineralization of plaque [Duke et al, 1979] and increased uptake of fluoride by dental enamel [Chowet al, 1981;Mellberg and Chomicki, 1985], Similarly, calcium lactate and fluoride were found to have additive protective effects on caries develop ment in rats [van der Hoeven, 1985].…”
Section: Discussionmentioning
confidence: 99%
“…These studies, amongst others, fi rmly established the anti-caries properties of CaGP. Subsequently, CaGP was included in a number of dentifrice formulations as a component of the anti-caries system, usually in conjunction with fl uoride as sodium monofl uorophosphate (SMFP), and caries clinical studies have been conducted to assess the anti-caries effi cacy of the system [Naylor and Glass, 1979;Mainwaring and Naylor, 1983].Several possible mechanisms for the anti-caries properties of CaGP have been investigated. These include elevation of plaque calcium and phosphate concentrations [Duke et al, 1979], plaque pH buffering [Bowen, 1972],…”
mentioning
confidence: 99%